Covalent dimerization of interleukin‐like epithelial‐to‐mesenchymal transition (EMT) inducer (ILEI) facilitates EMT, invasion, and late aspects of metastasis. (14th September 2017) - Kral, Maria; Klimek, Christoph; Kutay, Betül; Timelthaler, Gerald; Lendl, Thomas; Neuditschko, Benjamin; Gerner, Christopher; Sibilia, Maria; Csiszar, Agnes
Abstract : The interleukin‐like epithelial‐to‐mesenchymal transition (EMT) inducer (ILEI)/FAM3C is a member of the highly homologous FAM3 family and is essential for EMT and metastasis formation. It is upregulated in several cancers, and its altered subcellular localization strongly correlates with poor survival. However, the mechanism of ILEI action, including the structural requirements for ILEI activity, remains elusive. Here, we show that ILEI formed both monomers and covalent dimers in cancer cell lines and in tumors. Using mutational analysis and pulse‐chase experiments, we found that the four ILEI cysteines, conserved throughout the FAM3 family and involved in disulfide bond formation were essential for extracellular ILEI accumulation in cultured cells. Modification of a fifth cysteine (C185), unique for ILEI, did not alter protein secretion, but completely inhibited ILEI dimerization. Wild‐type ILEI monomers, but not C185A mutants, could be converted into covalent dimers extracellularly upon overexpression by intramolecular‐to‐intermolecular disulfide bond isomerization. Incubation of purified ILEI with cell culture medium showed that dimerization was triggered by bovine serum in a dose‐ and time‐dependent manner. Purified ILEI dimers induced EMT and trans‐well invasion of cancer cells in vitro . In contrast, ILEI monomers and the dimerization‐defective C185A mutant affected only cell motility as detected by scratch assays and cell tracking via time‐lapse microscopy. Importantly, tumor cells overexpressing wild‐type ILEI caused large tumors and lung metastases in nude mice, while cells overexpressing the dimerization‐defective C185A mutant behaved similar to control cells. These data show that covalent ILEI self‐assembly is essential for EMT induction, elevated tumor growth, and metastasis. Abstract : Interleukin‐like epithelial‐to‐mesenchymal transition (EMT) inducer (ILEI) is present as monomers and covalent dimers. Monomers can be converted to covalent dimers extracellularly, triggered by serum factors. Purified ILEI provides in vitro evidence that only covalent ILEI dimers induce EMT and invasiveness. Cysteine 185 is important for dimerization. Utilizing a C185A dimerization‐mutant ILEI reveals that ILEI dimerization is necessary for EMT, elevated tumor growth, and metastasis in vivo .